静脈穿刺に用いる駆血帯装着時の駆血圧と静脈怒張度との関係 - 加藤 晶子; 森 將晏 (日本看護技術学会誌, 2009)
To estimate the appropriate tourniquet pressure for venipuncuture, tourniquets made of gum-tube or elastic belt were fastened around the upper arm of 12 healthy subjects with the length adjusted to 95% to 75% of the upper arm circumference. Tourniquet pressure, vein overswelling score and pain score were recorded. Tourniquet pressure was linearly increased according to the fastening strength in both tourniquets. Average pressures after fastening the gum-tube at 95% and at 75% of upper arm circumference were 38.6 mmHg and 166.4 mmHg respectively, whereas the average pressures after fastening an elastic belt at 95% and at 75% of upper arm circumference were 20.1 mmHg and 121.2 mmHg respectively. Using the gum-tube fastening, 9 subjects showed detectable overswelling at 90% (68.2mmHg) and overswelling increased at 85% (92.6mmHg) tightening. Thereafter, overswelling did not further increase at 80% and 75% tightening. Using the elastic belt fastening, eight subjects showed detectable overswelling at 90% (45.6mmHg) and overswelling increased at 80% (94.9mmHg) tightening. Thereafter, overswelling did not increase at 75% tightening. These data suggested that the appropriate tourniquet pressure for venipuncture ranges from 70-95 mmHg in gum-tube tourniquet and from 45-95 mmHg for elastic belt tourniquet. If the tourniquet pressure is greater than the range described here, overswelling of the vein did not increase but subjective pain perception increased in the subjects. 静脈穿刺に適切な駆血帯を締める強さを検討する目的で，留め金つきゴム管駆血帯 (ゴム管) とバックルつきニットゴム製駆血帯 (ベルト) を用い，駆血帯を留める位置を駆血部の腕周囲径の95～75％まで5％ずつ短くしたときの駆血圧，静脈怒張度，苦痛度等について12名の健康成人を対象にして検討した．駆血圧は両駆血帯ともに締めつける長さが短くなるにつれてほぼ直線的に増加し，ゴム管では周囲径の95％で平均38.6mmHg，75％では平均166.4mmHgであった．一方ベルトは，95％で平均20.1mmHgを示し，75％では平均121.2mmHgであった．静脈怒張度は，ゴム管では駆血前は全員「血管の触知ができない」で，90％ (68.2mmHg) で「少し血管の触知ができる」以上が9名となり，85％ (92.6mmHg) では11名と増加したが，それ以上短くしても怒張度は増加しなかった．ベルトにおいても90％ (45.6mmHg) で「少し血管の触知ができる」以上が8名となり，80% (94.9mmHg) までは「十分血管の触知ができる」が増加したが，75％ではそれ以上増加しなかった．駆血圧との関係でみると，静脈穿刺に適切な怒張度を得るためにはゴム管で約70～95mmHg，ベルトで45～95mmHgの駆血圧が必要で，それ以上強く締めても怒張度は増加せず，苦痛度が増加するのみであった．